THE DEVELOPMENT OF ENGLISH FOR BEGINNER THROUGH POCKETBOOK MEDIA TO IMPROVE STUDENT LEARNING PRIMARY RESULTS - Jihan Alhanin Choir; Agus Zaenul Fitri (Al-Bidayah : jurnal pendidikan dasar Islam, 2020)
Students' difficulty in understanding English language as a subject usually leads to poor learning outcomes. The problem is, however, observed to be getting worse due to the unavailability of suitable learning media for educators and students. This research was, therefore, conducted to develop an English for Beginner pocketbook media to improve student learning outcomes. Meanwhile, pocketbook media is an alternative packaging of information through the use of user efficiency elements. This research was developed based on the Borg & Gall model with the data collected using questionnaires, tests, and documentation and analyzed through Independent Sample T-test. The results showed the sig. (2-tailed) < sig. level (0,000 < 0.05), therefore, Ha was accepted while H0 was rejected. It was discovered that average students learning outcomes increased to 83,4 and learning completeness by 83.33% after receiving the treatment in the form of the English for Beginner pocketbook media. This shows this material is feasible to be implemented as a learning medium due to its effectiveness in improving the learning outcomes of fifth-grade students of MI Masaran 1 Trenggalek.